1991
DOI: 10.1007/bf03350286
|View full text |Cite
|
Sign up to set email alerts
|

Histiocytosis x of the hypothalamus

Abstract: An unusual case of cutaneous and hypothalamic histiocytosis X (HX) is reported. The hypothalamic involvement occurred as a tumor that mimicked a chiasm glioma on computed tomography angioscanning. Magnetic resonance imaging after gadolinium injection localized the tumor within the third ventricle floor. The HX origin of the tumor was confirmed by histological examination of hypothalamic biopsies obtained by transventricular endoscopy. The results of endocrine evaluation were consistent with anterior panhypopit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Anterior pituitary hormonal deficiencies have been described in up to 20% of patients with LCH almost always associated with DI [2,3,[5][6][7][8][9]. Only a very few cases of isolated anterior pituitary hormone deficiencies, without the coexistence of DI, have been reported in the literature [10]. In cases of endocrine involvement, systemic treatment appears to be of little benefit in controlling the progression of the disease, while established endocrine abnormalities are considered to be permanent [3,11,12].…”
Section: Introductionmentioning
confidence: 98%
“…Anterior pituitary hormonal deficiencies have been described in up to 20% of patients with LCH almost always associated with DI [2,3,[5][6][7][8][9]. Only a very few cases of isolated anterior pituitary hormone deficiencies, without the coexistence of DI, have been reported in the literature [10]. In cases of endocrine involvement, systemic treatment appears to be of little benefit in controlling the progression of the disease, while established endocrine abnormalities are considered to be permanent [3,11,12].…”
Section: Introductionmentioning
confidence: 98%
“…Pan-hypopituitarism, as in our case, is rare. Pituitary insufficiency is explained by the lack of secretion of hormones from the hypothalamus and pituitary [4]. e incidence of LCH involving the thyroid gland, either as an isolated lesion or as a part of a multisystemic disease, is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…There are several patients presented in the literature who had APD and DI when LCH was diagnosed [16][17][18][19]. Tabarin et al reported a patient with hypothalamic LCH who had APD without DI; however, it was not isolated since cutaneous involvement was present [20].…”
Section: Discussionmentioning
confidence: 99%